The matter of wombs renting is a juristic study - Diyaree Abdulrazzaq Kaka Hama (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
This research (the matter of wombs renting is a juristic study) includes an introduction in which the importance of the subject and the plan are presented, on which I consequently go. And four chapters: The first chapter gives an accurate talk about renting wombs. It is a downward incident which is a strange outcome of Western cultures, and it has to be put in legitimate controls for this matter and it has to be studied in the light of Islamic jurisprudence like other issues, and explaining those bases and principles resembling such matters in terms of law, as well as exploring the moral caveats that result from these matters. The second Chapter covers the individuals of this issue, such as: talking on the rented mother, and the close mother. The Third Chapter comprises jurisprudential adapting for the matter about taboo images, and law of renting on the mahram (those who cannot be married). The fourth chapter talks about the consequences on this issue of the provisions of legitimacy as descent, the child, and the issue of alimony, the issue of inheritance, and other matters related to this issue. In the end, I presented the main findings I arrived at, throughout my study of this new matter which is worthy exploring and researching.